Characterisation of Cladonia rangiferina transcriptome and genome, and the effects of dehydration and rehydration on its gene expression - Junttila, Sini (fi=Turun yliopisto|en=University of Turku|, 2016)
Lichens are symbiotic organisms, which consist of the fungal partner and the photosynthetic partner, which can be either an alga or a cyanobacterium. In some lichen species the symbiosis is tripartite, where the relationship includes both an alga and a cyanobacterium alongside the primary symbiont, fungus. The lichen symbiosis is an evolutionarily old adaptation to life on land and many extant fungal species have evolved from lichenised ancestors. Lichens inhabit a wide range of habitats and are capable of living in harsh environments and on nutrient poor substrates, such as bare rocks, often enduring frequent cycles of drying and wetting. Most lichen species are desiccation tolerant, and they can survive long periods of dehydration, but can rapidly resume photosynthesis upon rehydration. The molecular mechanisms behind lichen desiccation tolerance are still largely uncharacterised and little information is available for any lichen species at the genomic or transcriptomic level. The emergence of the high-throughput next generation sequencing (NGS) technologies and the subsequent decrease in the cost of sequencing new genomes and transcriptomes has enabled non-model organism research on the whole genome level. In this doctoral work the transcriptome and genome of the grey reindeer lichen, Cladonia rangiferina, were sequenced, de novo assembled and characterised using NGS and traditional expressed sequence tag (EST) technologies. RNA extraction methods were optimised to improve the yield and quality of RNA extracted from lichen tissue. The effects of rehydration and desiccation on C. rangiferina gene expression on whole transcriptome level were studied and the most differentially expressed genes were identified. The secondary metabolites present in C. rangiferina decreased the quality – integrity, optical characteristics and utility for sensitive molecular biological applications – of the extracted RNA requiring an optimised RNA extraction method for isolating sufficient quantities of high-quality RNA from lichen tissue in a time- and cost-efficient manner. The de novo assembly of the transcriptome of C. rangiferina was used to produce a set of contiguous unigene sequences that were used to investigate the biological functions and pathways active in a hydrated lichen thallus. The de novo assembly of the genome yielded an assembly containing mostly genes derived from the fungal partner. The assembly was of sufficient quality, in size similar to other lichen-forming fungal genomes and included most of the core eukaryotic genes. Differences in gene expression were detected in all studied stages of desiccation and rehydration, but the largest changes occurred during the early stages of rehydration. The most differentially expressed genes did not have any annotations, making them potentially lichen-specific genes, but several genes known to participate in environmental stress tolerance in other organisms were also identified as differentially expressed.

Jäkälä on symbioosi, johon kuuluu sieniosakas ja yhteyttävä osakas, joka voi olla joko levä tai syanobakteeri. Joissakin jäkälälajeissa symbioosiin kuuluu kolme osakasta, eli sekä levä että syanobakteeri ovat mukana symbioosissa primääriosakkaan eli sienen kanssa. Jäkäläsymbioosi on evolutiivisesti vanha sopeutuma elämään maan päällä ja monet nykyiset sienilajit ovat kehittyneet jäkälistä. Jäkälät elävät hyvin vaihtelevissa elinympäristöissä ja pystyvät selviämään ankarissakin olosuhteissa sekä vähäravinteisilla kasvualustoilla, kuten paljaan kiven päällä. Elinolosuhteidensa vuoksi monet jäkälälajit joutuvat sopeutumaan säännölliseen kuivumisen ja kastumisen vaihteluun. Enemmistö jäkälistä kestää hyvin kuivuutta ja selviää elossa pitkiäkin aikajaksoja ilman vettä. Kastuessaan jäkälät pystyvät kuitenkin nopeasti jatkamaan yhteyttämistä. Molekulaariset mekanismit, jotka vaikuttavat jäkälien kuivuuden sietoon, ovat edelleen suurelta osin tuntemattomia ja jäkälistä on ylipäänsä vähän tietoa saatavilla genomi- ja transkriptomitasolla. NGS-sekvensointimenetelmien kehittäminen ja sitä seurannut genomi- ja transkriptomisekvensoinnin hinnan lasku ovat mahdollistaneet ei-malliorganismien tutkimisen koko genomin tasolla. Tässä väitöskirjatutkimuksessa harmaaporonjäkälän, Cladonia rangiferinan, transkriptomi ja genomi sekvensointiin, de novo assembloitiin ja karakterisoitiin käyttäen NGS-tekniikkaa sekä perinteistä EST-sekvensointitekniikkaa. RNA:n eristysmenetelmiä optimoitiin jäkälästä eristetyn RNA:n saannon ja laadun parantamiseksi. Kastumisen ja kuivumisen vaikutuksia C. rangiferinan geenien ilmentymiseen tutkittiin koko transkriptomin tasolla ja geenit, joiden ilmentymistaso muuttui eniten, pystyttiin tunnistamaan. Cladonia rangiferinan sisältämät sekundäärimetaboliitit heikensivät eristetyn RNA:n laatua ja täten tarvittiin jäkälälle optimoitu RNA:n eristysmenetelmä, jotta pystyttiin eristämään tarvittava määrä hyvälaatuista RNA:ta edullisesti ja riittävän nopeasti. C. rangiferinassa aktiivisia biologisia toimintoja sekä reaktioteitä pystyttiin tunnistamaan transkriptomin de novo assemblyn avulla. Genomin de novo assemblyssä saatiin tulokseksi assembly, joka koostui pääasiassa sieniosakkaan geeneistä. Se oli kuitenkin kohtuullisen laadukas, samankokoinen kuin muista jäkälien sieniosakkaista julkaistut genomit sekä sisälsi suurimman osan tärkeimmistä konservoituneista eukaryoottigeeneistä. Jokaisesta tutkitusta harmaaporonjäkälän kastumis- ja kuivumisvaiheesta pystyttiin tunnistamaan eroja geenien ilmentymisessä, mutta suurimmat erot tapahtuivat kastumisen alkuvaiheissa. Geeneille, joiden erot olivat suurimmat, ei löytynyt sekvenssikuvausta, joten ne saattavat olla jäkäläspesifisiä geenejä. Tutkimuksessa havaittiin eroja myös sellaisten geenien ilmentymisessä, joiden tiedetään osallistuvan erilaisten ympäristöperäisten tekijöiden stressinsietokyvyn muodostumiseen muissa organismeissa.